Recent Advances in the Development of Catalytic Methods that Construct Medium-Ring Lactams, Partially Saturated Benzazepines and Their Derivatives - Mazumdar, Wrickban; Driver, Tom G. (Synthesis, 2021)
Recent catalytic methods to construct medium-sized lactams and partially saturated benzazepines and their derivatives are surveyed. The review is divided into the following sections:1 Introduction2 Non-Transition-Metal-Catalyzed Reactions2.1 Beckmann Rearrangement2.2 Non-Beckmann Rearrangement Reactions2.3 Multicomponent reactions3 Transition-Metal-Catalyzed Reactions3.1 Gold-Catalyzed Reactions to Access Medium-Sized N-Heterocycles3.2 Reactions Involving a Metal η3-Complex Catalytic Intermediate3.3 Transition-Metal-Catalyzed Reactions of Strained Cycloalkanes4 Conclusions
Keywords: Beckmann rearrangement; caprolactam; benzazepine; benzazepinone; medium-ring N-heterocycle